2014
DOI: 10.1093/mnras/stu1695
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spatial resolution on optical and near-IR studies of stellar clusters: implications for the origin of the red excess

Abstract: Recent ground based near-IR studies of stellar clusters in nearby galaxies have suggested that young clusters remain embedded for 7 − 10 Myr in their progenitor molecular cloud, in conflict with optical based studies which find that clusters are exposed after 1 − 3 Myr. Here, we investigate the role that spatial resolution plays in this apparent conflict. We use a recent catalogue of young (< 10 Myr) massive (> 5000 M ⊙ ) clusters in the nearby spiral galaxy, M83, along with Hubble Space Telescope (HST) imagin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…If the clusters are exposed but there is still Hα emission within the aperture from the nearby gas, a fit using Hα may still be more accurate than without. Bastian et al (2014a) and Bastian, Hollyhead & Cabrera-Ziri (2014b) found a similar effect in the nebular continuum in the near-IR when studying YMCs.…”
Section: The Problem With Hαmentioning
confidence: 61%
See 1 more Smart Citation
“…If the clusters are exposed but there is still Hα emission within the aperture from the nearby gas, a fit using Hα may still be more accurate than without. Bastian et al (2014a) and Bastian, Hollyhead & Cabrera-Ziri (2014b) found a similar effect in the nebular continuum in the near-IR when studying YMCs.…”
Section: The Problem With Hαmentioning
confidence: 61%
“…These clusters should be visible in the near-IR, however, studies that attempted to use IR data, e.g. Grosbøl & Dottori (2013), using aperture photometry as with optical data, have proven unreliable due to spatial resolution effects (Bastian et al 2014a). Despite this, space-based instruments with high spatial resolution [e.g.…”
Section: Infrared Age Dating Of Clustersmentioning
confidence: 99%
“…However, the coarser spatial resolution of the F160W might lead to an over-estimation of the photometry in this band (see e.g. Bastian et al 2014, , but with aperture photometry). This effect will be discussed in section 5.1.…”
Section: Star Cluster Formation Efficiency In the Tdgsmentioning
confidence: 99%
“…Some F160W flux measurements might have been contaminated by regions that are very close to the clusters and that are not included in the other bands, which might affect the derivation of the physical quantities (e.g. Bastian et al 2014, in the case of aperture photometry).…”
Section: Effect Of Including the F160w Bandmentioning
confidence: 99%
“…However, with the small aperture sizes used, r ≈ 9 pc, crowding effects are not expected to significantly bias the statistical results (Randriamanakoto et al 2013). The reasonably small apertures also help in mitigating filter-dependent resolution effects (Bastian et al 2014). Figure 2a shows the luminosity function of all our YMCs fitted with Φ(L)dL ∝ L −α dL.…”
Section: Ages and Masses Of The Ymcsmentioning
confidence: 96%